The Influence of Work Behavior, Leadership Style, and Commitment on Employee Performance - Marsuhin Marsuhin (Innovation Business Management and Accounting Journal, 2025)
This study aims to analyze the influence of work behavior, leadership style, and commitment on employee performance at Koperasi Sentral Asia, Lumajang, using multiple linear regression analysis methods and data obtained directly from respondents through questionnaires distributed to the employees of Koperasi Sentral Asia in Lumajang. The research findings indicate that work behavior and commitment have a significantly positive effect on employee performance. In contrast, leadership style does not show a significant impact on employee performance. Furthermore, the study reveals that work behavior, leadership style, and commitment collectively have a significant influence on employee performance. These findings provide valuable insights for management in effectively managing and improving employee performance through appropriate work behavior approaches and strengthening employee commitment.